Cosmetic benefits of astaxanthin on humans subjects - Tominaga, Kumi; Hongo, Nobuko; Karato, Mariko; Yamashita, Eiji (Acta biochimica Polonica, 2012)
Two human clinical studies were performed. One was an open-label non-controlled study involving 30 healthy female subjects for 8 weeks. Significant improvements were observed by combining 6 mg per day oral supplementation and 2 ml (78.9 μM solution) per day topical application of astaxanthin. Astaxanthin derived from the microalgae, Haematococcus pluvialis showed improvements in skin wrinkle (crow's feet at week-8), age spot size (cheek at week-8), elasticity (crow's feet at week-8), skin texture (cheek at week-4), moisture content of corneocyte layer (cheek in 10 dry skin subjects at week-8) and corneocyte condition (cheek at week-8). It may suggest that astaxanthin derived from H. pluvialis can improve skin condition in all layers such as corneocyte layer, epidermis, basal layer and dermis by combining oral supplementation and topical treatment. Another was a randomized double-blind placebo controlled study involving 36 healthy male subjects for 6 weeks. Crow's feet wrinkle and elasticity; and transepidermal water loss (TEWL) were improved after 6 mg of astaxanthin (the same as former study) daily supplementation. Moisture content and sebum oil level at the cheek zone showed strong tendencies for improvement. These results suggest that astaxanthin derived from Haematococcus pluvialis may improve the skin condition in not only in women but also in men.